ANALISIS PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KEMUNGKINAN FINANCIAL DISTRESS - Rusdan Radifan; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This study aimed to axamine the impact of the characteristics of good corporate governance as managerial ownership, institutional ownership, the proportion of independent commissioners, the number of boards of directors, the size of audit committee, composition of independent commissioners in the audit committee, the number of audit committee meetings, and a number of financial experts on audit committee the possibility of financial distress. This study uses the size of the company as a control variable. The population in this study includes all companies listed on the Bursa Efek Indonesia  (BEI) in 2013. The samples conducted  by purposive sampling  method. Criteria for financial distress company is a company with negative earnings per share in the reporting period. The sample used in this study were non-financial companies that have availability annual report in 2013. The total sample is 90 companies, which consists of 45 companies financial distress as well as 45 non-financial companies with similar industry distress and accounting reporting period. The analysis technique used is logistic regression. The results of anlysis showed that the variables of institutional ownership, number of board of directors, the composition of independent commissioners in the audit committee, the number of audit committee meetings, and the number of audit committee financial expert in a significant negative effect on the possibility of financial distress, while variable managerial ownership,  the proportion of independent commisioners, and the size of the audit committee did not significantly affect the financial distress.